Assessment and evaluation - Collett, Pippa (Henry Stewart Talks, 2009)
Setting objectives, The role of market research, Sponsorship selection process |Selection and exclusion criteria, Tangible and intangible assets, Evaluation approach and program development, Measurement criteria